TINJAUAN TEORETIK TENTANG KOMITMEN ORGANISASI GURU - Rais Hidayat (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2017)
ABSTRACTTeachers' organizational commitment is the key to the implementation of quality education. Without high organizational commitment of teacher, the implementation of quality education is unlikely to materialize. Therefore, a clear description and conception of teachers' organizational commitment is needed. The purpose of this research is to describe the teachers' organizational commitment in depth decription. This research uses literature review method. The results of the research were then presented to answer the 3 research problems: the nature of teachers organizational commitment, the processes and factors that shaped the organizational commitment of teachers, and the ways to develop and enhance the organizational commitment of teachers.Keywords: organizational commitment, theoretical review, literature methodABSTRAKKomitmen organisasi guru merupakan kunci pelaksanaan pendidikan yang bermutu. Tanpa komitmen organisasi yang tinggi, pelaksanaan pendidikan bermutu tidak mungkin terwujud. Oleh karena itu, deskripsi dan konsepsi yang jelas tentang komitmen organisasi guru sangat diperlukan. Tujuan penelitin ini untuk mendeskripsikan komitmen organisasi guru secara lebih mendalam. Kajian teoretik ini menggunakan metode kajian literatur. Hasil kajian kemudian dipaparkan untuk menjawab 3 rumusan permasalahan penelitian yaitu: tentang hakikat komitmen organisasi guru, proses dan faktor-faktor yang membentuk komitmen organisasi guru, dan tentang cara-cara mengembangkan dan meningkatkan komitmen organisasi guru.Kata kunci: komitmen organisasi, tinjauan teoretik, metode literatur